2002
DOI: 10.1021/jp0114790
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Monomer and Dimer of Cyclo[(−l-Phe-d-Ala−)n] and Cyclo[(−l-Phe1-d-MeN-Ala2−)n] (n = 3−6)

Abstract: The monomer and dimer structures of cyclo[(-L-Phe 1 -D-Ala 2 ) n -] and cyclo[(-L-Phe 1 -D-Me N-Ala 2 ) n -] (n ) 3-6) were studied by using the semiempirical molecular orbital AM1 method and the density functional B3LYP method. The structural characteristics of these molecules were revealed, some of which are not yet confirmed experimentally. The influences of the substituents and ring size on molecular structure and the self-assembly process are discussed in detail. The inherent impetus for these molecules t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 19 publications
3
44
1
Order By: Relevance
“…The number of hydrogen bonds during the initial 1 ns of constrained MD is not plotted in the figure, as it is expected to be eight for all the systems. The quantum mechanical studies by Chen et al 10 showed that the conformation for the optimized cyclo [(-L-Phe-D-N-MeAla-) 4 -] is distorted to a certain extent compared to that for cyclo [(-L-Phe-D-Ala-) 4 -]. It was observed that the angles of NH and CO with respect to the ring plane in the capped ring depart farther than that found for the uncapped ring.…”
Section: Resultsmentioning
confidence: 99%
“…The number of hydrogen bonds during the initial 1 ns of constrained MD is not plotted in the figure, as it is expected to be eight for all the systems. The quantum mechanical studies by Chen et al 10 showed that the conformation for the optimized cyclo [(-L-Phe-D-N-MeAla-) 4 -] is distorted to a certain extent compared to that for cyclo [(-L-Phe-D-Ala-) 4 -]. It was observed that the angles of NH and CO with respect to the ring plane in the capped ring depart farther than that found for the uncapped ring.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the semiempirical molecular orbital method is the only option. Our previous study has proved that cyclo[(-l-Phe-d-Ala-) 4 ] and its dimers optimized by both semiempirical molecular orbital AM1 method and density functional method B3LYP/6-31G* show similar characteristics in structures and energies [18]. In this work, we further confirmed the adaptability of AM1 method; thus the structural and energetic comparisons of H-bonds in the antiparallel l-l, d-d and parallel l-d dimers were performed by using either the semiempirical molecular orbital AM1 method and the density functional method B3LYP [32] with 6-31g, 6-31g ** basis sets and PBE1PBE25 [33]/6-31g ** .…”
Section: Model and Methodsmentioning
confidence: 99%
“…Based on the aforementioned discussion, the parallel dimer (l-d) and the antiparallel dimers [18] 4 ], and a series of tubular oligomers, from trimer to decamer, were constructed according to parallel, antiparallel and parallel-antiparallel mixing stacking schemes. All the oligomers retained C 4 symmetry and the distance between adjacent rings was initially set to ϳ5.0 Å.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Recently, a new class of organic compounds has been reported in which amino acid unites make a macrocycle named cyclic peptide. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Cyclic peptides as a group of the cyclic compounds are of wide research interest. 10 These compounds have several biological activities such as antibacterial agent, [11][12][13] inhibitors of cell growth 14 enzymes, 15 antiviral, 16 antifungal, 17 immunosuppressant 18 antinociceptive properties 19 anthelmintic and cytotoxic agents.…”
Section: Introductionmentioning
confidence: 99%